Pneumomediastinum and Pneumothorax as Relevant Complications of Sub-Intensive Care of Patients with COVID-19: Description of a Case Series - Maria Gabriella Coppola; Marina Lugarà; Stefania Tamburrini; Pasquale Madonna; Claudio Panico; Giuseppe Noschese; Eduardo Pone (Medicina, 2021)
Lung failure has been the most common cause of hospitalization for COVID-19. Yet, bilateral interstitial pneumonia has not been the only cause of lung failure of these inpatients, and frequently they develop other illnesses associated with COVID-19. Pulmonary embolism has been the most looked for in the world, but rarely other pneumological diseases, such as pneumothorax and pneumomediastinum, have been described and associated with a worsening prognosis. We here report our clinical experience associated with the occurrence of pneumothorax and pneumomediastinum in a cohort of inpatients hospitalized in our division of medicine in a regular ward or in a sub-intensive ward.